Rating User Interface and Universal Instructional Design in MOOC Course Design - Meyer, Richard; Gaskill, Martonia; Vu, Phu (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2015)
This study examines how college students rate Massive Open Online Courses (MOOCs) in terms of User Interface Design and Universal Instructional Design. The research participants were 115 undergraduate students from a public midwestern university in the United States. Each participant evaluated three randomly chosen MOOCs, all of which were developed on the Coursera platform, using rubrics for User Interface Design and Universal Instructional Design. The results indicated that students had an overall positive impression of each MOOC’s course design. This study concludes that overall course design strategies are not associated with the massive dropout rates currently documented in MOOC learning environments. The authors suggest the use of appropriate instructional design principles be further explored.